Performance Evaluation of Traveling Wave Fault Locator for a 220kV Hoa Khanh-Thanh My Transmission Line - Le, K. H.; Vu, P. H. (Engineering, Technology & Applied Science Research, 2018)
This paper presents the traveling wave based fault location methods of SEL-400L, and SFL-2000 available on the market for a 66.9km, 220kV Hoa Khanh-Thanh My transmission line in Central Viet Nam, such as single-ended, and double-ended, all of which rely on measurements from inductive CTs and capacitive VTs. Focus was given on the building process of a Matlab Simulink model to evaluate these methods. Current and voltage signals were sent to an analog Chebyshev type II filter which passes higher frequency signals at 3kHz and rejects low frequencies signal at 50Hz. After that, these output signals are used in Clarke's transformation for getting 0 and α components. The detail coefficient of the selected components after DWT using Db4 wavelet at decomposition level 1 can be used to determine the fault types, the direction of fault and propose a crest-wave comparison solution to identify exactly the adjacent bus' reflected wave from the fault point's reflected wave for the fault location. Finally, the accuracy of fault location on the transmission line is reviewed by varying various parameters like fault type, fault location and fault resistance on a given power system model.